2004
DOI: 10.1196/annals.1332.019
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Receptor Modulation for Neuroprotection and Enhancement of Functional Recovery Following Brain Injury or Disease

Abstract: Despite the well-known adverse health effects of tobacco smoking, numerous studies have shown that nicotine, the principal pharmacologically active alkaloid in tobacco smoke, exerts neuroprotective properties in several animal models of neurodegeneration. Furthermore, cigarette smoking appears to significantly reduce the risk of developing Parkinson's disease in human subjects. We review the animal and human studies that investigated possible neuroprotective actions of nicotine and other nicotinic receptor ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Moreover, clinical data suggests their involvement in the pathogenesis of several disorders such as Alzheimer's disease (71), schizophrenia (72), Parkinson's disease (73), autoimmune autonomic neuropathy (74), and hereditary epilepsies (75). In this context, neuroprotective actions of nAChRs have been very well characterized (76). However, nicotine-exerted functions on developing neurons have not yet been thoroughly investigated.…”
Section: Cholinergic Receptorsmentioning
confidence: 99%
“…Moreover, clinical data suggests their involvement in the pathogenesis of several disorders such as Alzheimer's disease (71), schizophrenia (72), Parkinson's disease (73), autoimmune autonomic neuropathy (74), and hereditary epilepsies (75). In this context, neuroprotective actions of nAChRs have been very well characterized (76). However, nicotine-exerted functions on developing neurons have not yet been thoroughly investigated.…”
Section: Cholinergic Receptorsmentioning
confidence: 99%
“…While this fi nding is controversial, there is now ample evidence supporting a therapeutic benefi t from nicotine in Parkinson ' s 5 disease, and as a neuroprotectant to toxic insults such as excitotoxins [6][7][8][9][10] or Beta-amyloid derived peptides. [10][11][12] Understanding the mechanistic basis for these and other similarly interesting fi ndings, 13 including a cognitive benefi t from nicotine, 2 would be of obvious importance. The name " neuronal " was based principally on the tissue source of the DNA libraries from which these receptors were fi rst cloned, the brain, 14 but growing evidence indicates that cells other than neurons throughout the body express these receptors 15 , 16 including lymphocytes, macrophages, dendritic cells, adipocytes, keratinocytes, endothelial cells, and epithelial cells of the intestine and lung.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for neuroprotection is supported by numerous in vitro studies demonstrating NNR-mediated protection of cells from a variety of toxic challenges, including brain injury [15] , oxygen-glucose deprivation [16][17][18] , oxidative stress [16] , β-amyloid toxicity (reviewed in [14] ), 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) kainite and glutamate excitotoxicity [19][20][21] , ethanol exposure [22] , and nerve growth factor (NGF) deprivation [23][24][25][26] . Similarly, a number of studies using in vivo models have demonstrated neuroprotection by the reduction of β-amyloid expression in the APPsw mouse (a transgenic model of AD) [27] , surgically induced neuronal loss through nucleus basalis lesions [28] , chemically induced neurotoxicity mediated by MPTP toxicity and systemic kainic acid-induced excitotoxic effects (reviewed in [19,24] ), glutamate toxicity in the spastic HanWistar rat [29] , cerebral ischemia-reperfusion [30] , chronic ischemia models, and paraquat toxicity [31] .…”
Section: Preclinical Evidence For Neuroprotectionmentioning
confidence: 99%